ASSESSING THE EFFECTIVENESS OF DIFFERENT TRADITIONAL PROCESSING METHODS ON PROXIMATE COMPOSITION OF FRESHWATER CATFISH, MYSTUS NGASEP - NANAOBI, HEMAM; SAROJNALINI, CHUNGKHAM; DANIEL, N.; Romharsha, Hawaibam (Journal of the Inland Fisheries Society of India, 2026)
The aim of this study was to evaluate the effectiveness of three different traditional processing methods (steaming, smoking and frying) on proximate composition of the freshwater catfish, Mystus ngasep. A standard AOAC protocol was adapted to analyze the following proximate parameters in fish: moisture, crude protein, crude lipids and total ash. The results show that all three traditional processing methods had significantly (p<0.05) improved the proximate profile of fish. Although all treatment methods improved proximate contents, the highest level of moisture reduction (8.823%), highest crude protein content (61.433%), and highest total ash level (13.123%) were found in the smoked fish. Regarding crude lipid content, the highest concentration (37.833%) was observed in fried fish. Taken together, findings of this study would seem to suggest that all three processing methods help improve the nutritional value of this fish for consumption.